2016
DOI: 10.1016/j.ijcard.2016.07.263
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-13 infusion salvages the peri-infarct region to preserve cardiac function after severe myocardial injury

Abstract: Background Apelin-13 (A13) regulates cardiac homeostasis. However, the effects and mechanism of A13 infusion after an acute myocardial injury (AMI) have not been elucidated. This study assesses the restorative effects and mechanism of A13 on the peri-infarct region in murine AMI model. Methods 51 FVB/N mice (12 weeks, 30 g) underwent AMI. A week following injury, continuous micro-pump infusion of A13 (0.5 μg/g/day) and saline was initiated for 4-week duration. Dual contrast MRI was conducted on weeks 1, 2, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…They enhance the number of progenitor cells in the heart of post‐MI mice more efficiently than BMCs (Li et al, ). Consistent with this report, Chung et al () demonstrated that apelin‐13 could mobilize progenitor cells and improve the cardiac function after an acute myocardial injury. Moreover, after stem cell transplantation, increase in apelin expression in the heart or in the plasma of patients suffering from heart failure is associated with tissue repair.…”
Section: Apelin and Stem Cells: Effects On Cardiovascular Systemsupporting
confidence: 74%
“…They enhance the number of progenitor cells in the heart of post‐MI mice more efficiently than BMCs (Li et al, ). Consistent with this report, Chung et al () demonstrated that apelin‐13 could mobilize progenitor cells and improve the cardiac function after an acute myocardial injury. Moreover, after stem cell transplantation, increase in apelin expression in the heart or in the plasma of patients suffering from heart failure is associated with tissue repair.…”
Section: Apelin and Stem Cells: Effects On Cardiovascular Systemsupporting
confidence: 74%
“…Previous studies have demonstrated the accuracy of MEMRI in delineating infarct size in experimental MI [37,39,41,52,53] and its usefulness in interrogating pathophysiology, [30,54,55] but none have investigated such early changes after coronary occlusion in comparison to LGE-MRI. Our data suggest that myocytes within the AAR rapidly stop internalizing Mn 2+ under ischemic conditions, while our T1 mapping results show increased Mn 2+ uptake in the viable myocardium remote from the infarct.…”
Section: Discussionmentioning
confidence: 99%
“…Apelin-13 has a role in regulating the stress response with the BDNF by improving the HPA Axis and Hippocampal Glucocorticoid Receptor Dysfunctions (Dai et al 2018). Apelin has a protective effect against oxidative stress in heart myocardial cells as in many tissues (Chung et al 2016). Besides, the hormones apelin and BDNF also have regulatory roles in cardiac contraction (Szokodi et al 2002;Fulgenzi et al 2015).…”
Section: Discussionmentioning
confidence: 99%